Dicyemida and Orthonectida: Two Stories of Body Plan Simplification - Zverkov, Oleg A.; Mikhailov, Kirill V.; Isaev, Sergey V.; Rusin, Leonid Y.; Popova, Olga V.; Logacheva, Maria D.; Penin, Alexey A.; Moroz, Leonid L.; Panchin, Yuri V.; Lyubetsky, Vassily A.; Aleoshin, Vladimir V. (Frontiers in Genetics, 2019)
Two enigmatic groups of morphologically simple parasites of invertebrates, the Dicyemida (syn. Rhombozoa) and the Orthonectida, since the 19th century have been usually considered as two classes of the phylum Mesozoa. Early molecular evidence suggested their relationship within the Spiralia (=Lophotrochozoa), however high rates of dicyemid and orthonectid sequence evolution led to contradicting phylogeny reconstructions. Genomic data for orthonectids revealed that they are highly simplified spiralians and possess a reduced set of genes involved in metazoan development and body patterning. Acquiring genomic data for dicyemids, however, remains a challenge due to complex genome rearrangements including chromatin diminution and generation of extrachromosomal circular DNAs, which are reported to occur during the development of somatic cells. We performed genomic sequencing of one species of Dicyema, and obtained transcriptomic data for two Dicyema spp. Homeodomain (homeobox) transcription factors, G-protein-coupled receptors, and many other protein families have undergone a massive reduction in dicyemids compared to other animals. There is also apparent reduction of the bilaterian gene complements encoding components of the neuromuscular systems. We constructed and analyzed a large dataset of predicted orthologous proteins from three species of Dicyema and a set of spiralian animals including the newly sequenced genome of the orthonectid Intoshia linei. Bayesian analyses recovered the orthonectid lineage within the Annelida. In contrast, dicyemids form a separate clade with weak affinity to the Rouphozoa (Plathyhelminthes plus Gastrotricha) or (Entoprocta plus Cycliophora) suggesting that the historically proposed Mesozoa is a polyphyletic taxon. Thus, dramatic simplification of body plans in dicyemids and orthonectids, as well as their intricate life cycles that combine metagenesis and heterogony, evolved independently in these two lineages.